(untitled) (Journal of the College of Basic Education, 2026)
Vegetables, both summer and winter, are considered among the most important agricultural crops in the country because they are a main food for the population. Therefore, this research came to shed light on this crop in Al-Qadisiyah Governorate, where the research problem was (Is there an effect of human factors on the spatial variation of summer vegetables in Al-Qadisiyah Governorate? While the research hypothesis came to him that the variation exists in summer vegetable crops. The research divided crops into summer vegetables and winter vegetables and distributed the spatial variations of summer vegetables in the study area and the spatial variations of winter vegetables in Al-Qadisiyah Governorate, where it divided them into three categories. It was found that the highest category is spread in the southern regions of the study area, while the lowest category is in the form of a strip extending from east to west, while we find that the highest category in winter vegetables is confined to a narrow area in Al-Shamiya District, while the lowest category occupies most parts of the study. Where he used the factor analysis technique to know the effect of human factors on the variations of summer vegetables and concluded that there is a large variation in the areas of the study area. The first work was the urban population and the second factor was the rural population, which played a major role in the spatial variations of summer vegetables, while the rest of the human factors had a small effect on vegetables in Al-Qadisiyah Governorate